(untitled) - Ahmad, Shamim (Darya Ganj, New Delhi, 2005)
Contents of material: Computer in library management. Computer technology: Its advancement. Library sofware installation. Library network hardware. Terminal sofware. Online database. Online computer service. Computer selection and harware considerations. Multimedia catalogue and the computer. Electronic service delivery.
Keywords: Library science,Library administration; Data processing